Waste and the want: thoughts on the future - Thapar, Romesh (New Delhi, 1978)
A collection of articles, essays and comments prepared during the last ten years. They approach the crisis of today and the future from various converging points-food, housing, transport, health, living styles and value systems. The author argues that unless a continental country like India, facing a doubling of population in the next twenty-five years, understands the complexity of the challenge, many of the gains of planning and development will be lost. He also warns that our world cannot be divided into areas of unthinking waste and cruel want, but should be motivated towards a more meaningful and secure future, nationally and internationally.
Keywords: Social sciences